Cover Image for a special issue of Permafrost and Periglacial Processes: Transactions of the International Permafrost Association Number 3 - Angelopoulos, Michael; Overduin, Paul; Miesner, Frederieke; Grigoriev, Mikhail N.; Vasiliev, Alexander A. (Permafrost and Periglacial Processes, 2020)
The cover image is based on the Original Article* Recent Advances in the Study of Arctic Submarine Permafrost by Michael Angelopoulos** et al., https://doi.org/10.1002/ppp.2061.*** Source Credit: GRID‐Arendal; Overduin, et al. (2019); Obu, et al. (2019). This map was produced as part of the Nunataryuk project, which has received funding under the European Union’s Horizon 2020 Research and Innovation Programme under grant agreement no. 773421.